Health Care Empowerment in Increasing Community Knowledge Regarding Family Medicine Plants (Toga) for the Prevention of Hypertension at Puskesmas Dadok Tunggul Hitam, Padang - Yuanita Ananda; Mulyanti Roberto Muliantino; Zifriyanthi Minanda Putri; Muthmainnah Muthmainnah; Edo Gusdiansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Hypertension is often referred to as